Targeted therapy and immunotherapy for gastric cancer: rational strategies, novel advancements, challenges, and future perspectives - Dong Luo; Yunmei Liu; Zhengmao Lu; Lei Huang (Molecular Medicine)
Abstract Gastric cancer (GC) is one of the most common malignant tumors worldwide, and its treatment has been a focus of medical research. Herein we systematically review the current status of and advancements in targeted therapy and immunotherapy for GC, which have emerged as important treatment strategies in recent years with great potential, and summarize the efficacy and safety of such treatments. Targeted therapies against key targets in GC, including epidermal growth factor receptor (EGFR), human epidermal growth factor receptor 2 (HER2), and vascular endothelial growth factor (VEGF)/VEGF receptor (VEGFR), have shown remarkable therapeutic efficacies by inhibiting tumor progression and/or blood supply. In particular, markable breakthroughs have been made in HER2-targeting drugs for HER2-positive GC patients. To address intrinsic and acquired resistances to HER2-targeting drugs, novel therapeutic agents including bispecific antibodies and antibody–drug conjugates (ADC) targeting HER2 have been developed. Immunotherapy enhances the recognition and elimination of cancer cells by activating body anticancer immune system. Programmed cell death protein 1 (PD-1) and programmed cell death-ligand 1 (PD-L1) antibodies are the most commonly used immunotherapeutic agents and have been used with some success in GC treatment. Innovative immunotherapy modalities, including adoptive immune cell therapy, tumor vaccines, and non-specific immunomodulators therapy, and oncolytic viruses have shown promise in early-stage clinical trials for GC. Clinical trials have supported that targeted therapy and immunotherapy can significantly improve the survival and quality of life of GC patients. However, the effects of such therapies need to be further improved and more personalized, with advancement in researches on tumor immune microenvironment. Further studies remain needed to address the issues of drug resistance and adverse events pertaining to such therapies for GC. The combined application of such therapies and individualized treatment strategies should be further explored with novel drugs developed, to provide more effective treatments for GC patients.